(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Necrotizing enterocolitis (NEC) remains a major challenge in neonatology, particularly affecting premature infants and those with very low birth weight. This study analyzes trends in NEC incidence in Kazakhstan from 2020 to 2024, highlighting regional disparities and comparing them with international benchmarks. Data from perinatal centers and neonatal intensive care units (NICUs) indicate a significant increase in NEC cases, particularly in urban areas. Key recommendations include improving early diagnosis, standardizing feeding protocols, and promoting the use of breast milk to reduce NEC incidence and associated mortality rates. Objective The aim of this study was to examine surgical necrotizing enterocolitis in newborns. Materials and Methods This retrospective study analyzed data on NEC cases from neonatal intensive care units (NICUs) and perinatal centers across Kazakhstan from 2020 to 2024. Cases were categorized by region and year, with additional analysis focusing on neonatal characteristics such as birth weight and gestational age. Comparative analysis with international data was conducted to contextualize findings and identify potential areas for improvement in neonatal care practices. Results The analysis revealed a significant increase in NEC incidence in Kazakhstan, particularly in urban regions such as Almaty and Almaty Region. The number of cases peaked in 2023, with a 1.7-fold increase compared to 2020. Regional disparities were evident, with higher incidence rates in areas with better healthcare infrastructure. In less developed regions, such as Akmola and Turkestan, the growth was less pronounced but still present. Conclusion This study underscores the rising trend of NEC in Kazakhstan and the associated regional disparities. Adopting evidence-based preventive measures, enhancing healthcare infrastructure, and standardizing neonatal care protocols are essential for reducing NEC incidence and improving outcomes for this vulnerable population. BJMS, Vol. 24 No. 04 October’25 Page : 1119-1123